Case Report: Lipoma of the Tuber Cinereum Mimicking a Pituitary Gland Abnormality in a Girl With Central Precocious Puberty - Giacomozzi, Claudio; Nicolì, Lisa; Sozzi, Carlo; Piovan, Enrico; Maghnie, Mohamad (Frontiers in Endocrinology, 2021)
Introduction: Magnetic Resonance Imaging (MRI) is the best approach to investigate the hypothalamic-pituitary region in children with central precocious puberty (CPP). Routine scanning is controversial in girls aged 6-8 year, due to the overwhelming prevalence of idiopathic forms and unrelated incidentalomas. Cerebral lipomas are rare and accidental findings, not usually expected in CPP. We report a girl with CPP and an unusually shaped posterior pituitary gland on SE-T1w sequences. Case description: A 7.3-year-old female was referred for breast development started at age 7. Her past medical history and physical examination were unremarkable, apart from the Tanner stage 2 breast. X-ray of the left-hand revealed a bone age 2-years ahead of her chronological age, projecting her adult height prognosis below the mid parental height. LHRH test and pelvic ultrasound were suggestive for CPP. Routine brain MRI sequences, SE T1w and TSE T2w, showed the posterior pituitary bright spot increased in size and stretched upward. The finding was considered as an anatomical variant, in an otherwise normal brain imaging. Patients was started on treatment with GnRH analogue. At a thorough revaluation, imaging overlap with adipose tissue was suspected and a new MRI scan with 3D-fat-suppression T1w-VIBE sequences demonstrated a lipoma of the tuber cinereum, bordering a perfectly normal neurohypophysis. 3D-T2w-SPACE sequences, acquired at first MRI scan, would have provided a more correct interpretation if rightly considered. Conclusion: This is the first evidence, to our knowledge, of a cerebral lipoma mimicking pituitary gland abnormalities. Our experience highlights the importance of considering suprasellar lipomas in the MRI investigation of children with CPP, despite their rarity, should the T1w sequences show an unexpected pituitary shape. 3D-T2w SPACE sequences could be integrated into standard ones, especially when performing MRI routinely, to avoid potential misinterpretations.